Optimalisasi Pengembangan Pertanian Modern melalui Program ”Ngariung Tani” (Studi Kasus: Desa Sindangsari, Kecamatan Ciranjang, Kabupaten Cianjur) - Amelia Paramitha Mahanani; Lailatul Qodriyah Agne Verawati; Ni Made Armini Wiendi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Pertanian Bogor, 2020)
Currently the development of the concept of modern agriculture that is used combines two concepts, namely optimization of agricultural production through improving technology and improving the quality of crop yields using the latest technology that reflects the modernity in the agricultural world.